Triassic hydrothermal chimneys from the Ordos Basin of Northern China - Jiyuan You (Nature Portfolio, 2021)
Abstract Because few well-preserved hydrothermal chimneys have been found in terrestrial sedimentary rocks, research on paleo-thermal vents in geological history is relatively sparse. In this study, we present our original discovery of “hydrothermal chimneys” from the Chang 7 source rocks of the Triassic Yanchang Formation in the Ordos Basin, China, and provide the best evidence for deciphering hydrothermal activity preserved in the geological record (i.e., sedimentary rocks). Three possible chimney samples (i.e., samples 1551.6, 1551.6–2 and 1574.4) were collected for this study; they were interbedded with mudstones and oil shales, indicative of a deep-lake sedimentary environment. All three samples consist mainly of anhydrite, pyrite, and dolomite with the formation of mineral zoning across the walls of these structures, suggesting a sulfate-dominated stage and a carbonate-sulfide replacement stage. Moreover, their in situ geochemistry is characterized by high Eu, U, Th, Sr, Mn and U/Th ratios, which are typical indicators of hydrothermal vents. In addition, their S isotopes range from 7.89% to 10.88%, near the values of magma sulfur, implying a possible magmatic trigger for these hydrothermal vents. All this evidence shows that the Triassic sedimentary rocks of the Ordos Basin probably contain hydrothermal chimneys. Comparing ancient hydrothermal chimneys to modern hydrothermal chimneys, we should note the important implications of ancient chimneys; their formation mechanism may have been related to oil production, and they are possible indicators for future oil investigations. Further, they have great significance for studying the hydrothermal properties of primary dolomite.